Peripheral Eosinophilia in a Confirmed Case of Canine Acute Eosinophilic Dermatitis with Edema (Wells-Like Syndrome) - Pace A; Hendricks J (Veterinary Medicine: Research and Reports, 2025)
Ashley Pace, Jeanette Hendricks Department of Emergency and Critical Care, Advanced Critical Care Emergency and Specialty Services, Los Angeles, Culver City, CA, USACorrespondence: Ashley Pace, Department of Emergency and Critical Care, Advanced Critical Care Emergency and Specialty Services, Los Angeles, 9599 Jefferson Blvd, Culver City, CA, 90232, USA, Email ashley.pace@thirvepet.comAbstract: This case report describes a peripheral eosinophilia in a dog diagnosed with canine acute eosinophilic dermatitis with edema (CAEDE). A 1-year-old female spayed Terrier Mix canine presented as a referral from their primary care veterinarian for gastrointestinal signs that were recently treated, but ongoing, and a new dermatopathy. Her leukogram revealed an eosinophilia, not previously present at the onset of her gastrointestinal signs, and skin biopsies were consistent with diagnosis of CAEDE. Although the definitive cause of the development of CAEDE in this patient is ultimately unknown, the patient made a full recovery following treatment with corticosteroids over a three-week treatment course. To the authors’ knowledge, this is the first report of a confirmed diagnosis of CAEDE to present with peripheral eosinophilia on complete blood count (IDEXX Procyte Dx).Keywords: CAEDE, WLS, gastroenteritis, dermatopathy, metronidazole, eosinophil